Мова як феномен культури в контексті розвитку трансцендентальної феноменології - Григоришин, С. (Інститут філософії ім. Г.С. Сковороди НАН України, 2009)
The article is intended to investigate the concept of language as a phenomenon of culture in Max Scheler's phenomenology. Special attention is paid to analysis of this concept in the context of phenomenological reductions problems. The author describes the most important part of Scheler's conception of language, notably his theory of symbols. The role of this conception is defined by differentiation between the latter theory and Husserl's ideas about the place of language in the reductions method. The author argues that Scheler's concept of symbols can get round the obstacles of transcendental and eidetic reductions. Scheler interprets modifications of judgments only as modifications of individual pronouncements, but not as general pronouncements. It is a kind of treatment which has an influence upon whole phenomenological procedures, as well as upon the practice of phenomenological reductions. All these changes showes that phenomenology is also possible as a philosophy with a natural standpoint. The ground of such a view is Max Scheler's concept of language or, to be more precise, his theory of symbols and theory of judgment.